2008
DOI: 10.1523/jneurosci.2423-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain Dopamine Receptor Availability Is Inversely Associated with Novelty-Seeking Traits in Humans

Abstract: Novelty-seeking personality traits are a major risk factor for the development of drug abuse and other unsafe behaviors. Rodent models of temperament indicate that high novelty responding is associated with decreased inhibitory autoreceptor control of midbrain dopamine neurons. It has been speculated that individual differences in dopamine functioning also underlie the personality trait of novelty seeking in humans. However, differences in the dopamine system of rodents and humans, as well as the methods for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
153
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(173 citation statements)
references
References 74 publications
15
153
1
4
Order By: Relevance
“…Increased novelty seeking has been associated with increased risk for substance abuse and dependence 53,54 and with reduced midbrain dopamine receptor availability. 55 It is possible that novelty seeking may not be a strong risk factor for obesity because, unlike drugs of abuse, humans are exposed to food on a daily basis. According to the incentive-sensitization model of addiction, neural modification of the dopaminergic mesolimbic system by exposure to addictive drugs leads to hypersensitization of the reward system to drug-related stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Increased novelty seeking has been associated with increased risk for substance abuse and dependence 53,54 and with reduced midbrain dopamine receptor availability. 55 It is possible that novelty seeking may not be a strong risk factor for obesity because, unlike drugs of abuse, humans are exposed to food on a daily basis. According to the incentive-sensitization model of addiction, neural modification of the dopaminergic mesolimbic system by exposure to addictive drugs leads to hypersensitization of the reward system to drug-related stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive NS has been consistently linked to several neuropsychiatric disorders, including substance abuse (4), pathologic gambling (34), and eating disorders (35). Although the role of dopamine in driving NS behaviors has been largely confirmed (36)(37)(38), the involvement of other neurotransmitter systems remains scarcely studied. Positive correlation between mGluR5 availability ( 18 F-FPEB V T ) in limbic areas and temperament trait NS.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we did not observe associations between mGluR5 and NS in core regions of the reward circuitry, that is, the ventral tegmental area and the ventral striatum. Though this aspect of NS might primarily be related to dopamine signaling in humans (36), a recent study found that specific inactivation of mGluR5 signaling in D1-dopaminoceptive neurons abolishes NS behaviors in rodents (16), still suggesting that some dopaminergic-glutamatergic interactions are involved in NS behaviors. Lastly, the insula is a paralimbic region critically involved in determining the emotionalmotivational salience of various somatosensory stimuli (41), a key aspect of NS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report correlations between NS scores and interindividual differences in human dopaminergic brain regions in terms of functional activation (Abler et al, 2006;Naghavi et al, 2009), dopamine ligand binding (Zald et al, 2008) and connectivity with other brain regions (Cohen et al, 2009). To ensure that the genotypedependent differences in activation we describe are independent of NS, we repeated our statistical analyses including NS as an additional covariate.…”
Section: Imaging Responses To Perceptual Oddballsmentioning
confidence: 99%